2021
DOI: 10.1111/hel.12845
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of nodular gastritis in three classes of age

Abstract: Chronic active Helicobacter pylori gastritis plays a critical role in the development of gastric cancer. 1 Nodular gastritis is a particular type of H. pylori gastritis defined as antral gastritis with a unique protruding pattern resembling "goose flesh." Nodular gastritis is histopathologically characterized by prominent lymphoid follicles. [2][3][4]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Although endoscopic examination after eradication therapy is considered beneficial, regular endoscopic follow-up for all young patients treated with eradication is challenging. We have reported that the degree of histological inflammation in the gastric body varies among NG cases; not all NG has the same risk for diffuse-type gastric cancer, and patients with more severe inflammation in the gastric body may be considered high risk for gastric cancer [20]. In the present case, moderate inflammatory cell infiltration in the gastric body was observed in histological evaluations before eradication.…”
Section: Discussionmentioning
confidence: 43%
“…Although endoscopic examination after eradication therapy is considered beneficial, regular endoscopic follow-up for all young patients treated with eradication is challenging. We have reported that the degree of histological inflammation in the gastric body varies among NG cases; not all NG has the same risk for diffuse-type gastric cancer, and patients with more severe inflammation in the gastric body may be considered high risk for gastric cancer [20]. In the present case, moderate inflammatory cell infiltration in the gastric body was observed in histological evaluations before eradication.…”
Section: Discussionmentioning
confidence: 43%
“…NG is defined as antral gastritis with endoscopic findings typically characterized by a miliary pattern resembling “goose flesh” and is reportedly seen in NHPH 8 . NG is currently thought to be an early‐phase finding of H. pylori infection that is present in 80%–90% of young patients 14,15 . Since the HP group in the present investigation was limited to mild atrophy and contained young patients, the proportion of NG was presumably higher.…”
Section: Discussionmentioning
confidence: 77%
“…8 NG is currently thought to be an early-phase finding of H. pylori infection that is present in 80%-90% of young patients. 14,15 Since the HP group in the present investigation was limited to mild atrophy and contained young patients, the proportion of NG was presumably higher. However, there was no significant difference between the study groups.…”
Section: F I G U R E 3 (A)mentioning
confidence: 93%
“…The most common endoscopic lesions in children were nodularity (60.7%), of which 83.8% were positive for H. pylori. Nodularity has been reported in infected children, ranging from 21 to 93% [11,13,[33][34][35][36]. It is a typical endoscopic finding in children with H. pylori infection [34,37].…”
Section: Discussionmentioning
confidence: 99%